Penurunan Kecacatan Produk Akibat Human Error pada Proses Produksi Fashion Muslim - Yusuf Mauluddin; Lisna Novika Handayani (Institut Teknologi Garut, 2026)
CV. Rumah Jahit Zahra, is one of the convection industries that produces Muslim fashion with various models. The production process that occurs cannot be avoided from any errors that make the product defective. Based on preliminary data, product defects often occur in the production process at CV. Rumah Jahit Zahra. The main factor in the occurrence of product defects is operator error. The purpose of this study is to identify the factors that cause errors caused by operators and to correct errors to reduce the percentage of product defects using qualitative analysis with the SHERPA method and quantitative analysis with the HEART method. The results of this study, it can be seen that the HEP value of each production process is, quality control of 0.234, patterning cutting of 0.342, sewing of 0.416, steam of 0.256 and finishing of 0.18. And it is known from the results of the study that is often the cause or the highest factor in making mistakes occurs in the sewing process, with the job description Settup sewing machine, sewing parts (body, sleeves, collar), combining stitches according to their parts, paying attention to the age of use and wear of sewing machines that often occur errors so that improvements can be made by conducting checks on processes that often experience errors and making work procedures or technical instructions in the sewing process to reduce product defects due to operator errors.